COMPARATIVE STUDY OF INVERTING, EVERTING ANG INVAGINATION END-TO-END INTESTINAL ANASTOMOSIS IN EQUINE. - A.H.M, Salih; H., Shnain; B.I. , Al-Mufti, (The Iraqi Journal of Veterinary Medicine, 1989)
Three end-to-end intestinal anastomosis techniques have been compared in twenty horses, divided into three groups. Group one includes (8) horses for inverting, group two includes (8) horses for everting while third group includes (4) horses for invagination technique. Operations performed under general anaesthesia. Laparotomy done through the laft flank region. The jejunium was used to compare the three anastomotic techniques after enterectomy. A horse from inverted group is died due to paralytic ileus. Two horses from the everted group are also died due to ileus and leakage, while the four horses of the invaginated technique are died due to the slipping of the invaginated ends. The remaining horses of the inverting and everting groups were survived without any complications during the expriment . post-mortum have been studied at (15) and (30) days after the operations. The inverting techniques was free from adhesion and in some cases it was difficult to recognize the site of anastomosis, while the everting technique was associated with sever adhesion ranged from 25%-100% of their circumferences.